CORPORATE GOVERNANCE MECHANISMS AND ASSET DEPRECIATION VALUE OF QUOTED MANUFACTURING COMPANIES IN NIGERIA - Itoro Monday John; Clifford O. Ofurum; Solomon Egbe (American Journals Publishing, 2024)
This research study investigated the relationship between corporate governance mechanism and asset depreciation value of quoted manufacturing companies in Nigeria during the period 2010 to 2022. Corporate governance mechanism was used as the independent variable, while asset depreciation value serves as the dependent variable in the investigation within 13 years coverage. This research used ex-post facto design to carry out the investigation on 56 quoted manufacturing companies. The econometric statistical view version 10 software was used in the analyses. Results showed a positive and significant relationship between two dimensions of corporate governance mechanism (internal audit quality and auditor independence) and asset depreciation value, while positive and insignificant relationship was found between board of directors’ independence and asset depreciation value amongst others. The study recommended amongst others that shareholders of quoted manufacturing companies should review the current percentage in the appointment of non-executive directors.
Keywords: Board of directors’ independence. Internal audit quality. Auditor independence. Asset Depreciation value